Bruceine A induces cell growth inhibition and apoptosis through PFKFB4/GSK3β signaling in pancreatic cancer. (July 2021) - Zhang, Pengfei; Tao, Weiwei; Lu, Cai; Fan, Lu; Jiang, Qihang; Yang, Chengbin; Shang, Erxin; Cheng, Haibo; Che, Chuntao; Duan, Jinao; Zhao, Ming
Abstract: Pancreatic cancer is one of the most aggressive cancers with a poor prognosis and 5-year low survival rate. In the present study, we report that bruceine A, a quassinoid found in Brucea javanica (L.) Merr. has a strong antitumor activity against human pancreatic cancer cells both in vitro and in vivo . Human proteome microarray reveals that 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatase 4 (PFKFB4) is the candidate target of bruceine A and both fluorescence measurement and microscale thermophoresis suggest bruceine A binds to PFKFB4. Bruceine A suppresses glycolysis by inhibiting PFKFB4, leading to cell cycle arrest and apoptosis in MIA PaCa-2 cells. Furthermore, glycogen synthase kinase-3 β (GSK3β) is identified as a downstream target of PFKFB4 and an PFKFB4-interacting protein. Moreover, bruceine A induces cell growth inhibition and apoptosis through GSK3β, which is dysregulated in pancreatic cancer and closely related to the prognosis. In all, these findings suggest that bruceine A inhibits human pancreatic cancer cell growth via PFKFB4/GSK3β-mediated glycolysis, and it may serve as a potent agent for curing human pancreatic cancer. Graphical Abstract: ga1 Highlights: Bruceine A has a strong anti-pancreatic cancer activity both in vitro and in vivo . PFKFB4 is a target of bruceine A. GSK3β is a downstream signal and interacting protein of PFKFB4. Bruceine A inhibits pancreatic cancer cell growth via PFKFB4/GSK3β signaling.